Sex-selective Abortion: More than an Economic Issue - Wan, Stephanie (The Meducator, 2013)
The first ultrasound image of a fetus was published in the mid 1950s. Though this feat was a technical revolution because it incorporated sonar phenomena into the field of obstetrics, it was the image itself that resonated with individuals in and outside of the medical profession. For physicians, the development of the ultrasound allowed for prenatal detection of fetal abnormalities.For mothers, it provided a powerful visual to conceptualize the otherwise abstract physiological changes they were experiencing. No longer did the fetus’ health status depend on the mother’s account of her experience; the fetus became a patient in its own respect. Since then, a plethora of ethical questions have emerged, all of which center upon one basic question: should a fetus be considered a person? And if so, does a fetus have rights? So far, no simple answer has emerged. However, in countries where a dominant male preference exists, the lowering costs of ultrasound technology has led to ethical concerns over whether it is permissible to terminate a pregnancy on the basis of gender.